(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article provides a scientific and analytical overview of modern methodological approaches to developing pedagogical mastery and the possibilities of their application in the process of clinical education. During the study, the effectiveness of the competency-based approach, reflexive practice, simulation training, and interactive methods was studied. Specifically, in clinical education, a teacher’s pedagogical mastery is an important factor not only in conveying theoretical knowledge but also in forming students’ practical skills and professional decision-making competencies. According to statistical data, the application of simulation-based teaching methods in health education has been found to increase student academic performance by an average of 25-30%. At the same time, training based on reflexive analysis and modeling of clinical situations significantly develops the level of students’ critical thinking.